Covid persistente: una mirada actual - González R., Lourdes; Merino G., Consuelo; Códova B., Teresa; López N., Mercedes (Revista Hospital Clínico Universidad de Chile, 2024)
Persistent Covid (PC) represents a post-infectious complication of SARS-CoV-2 infection, characterized by symptoms that persist for more than 12 weeks after the acute phase. These symptoms, which include chronic fatigue, respiratory distress, cognitive dysfunction, and other multisystem effects, significantly impact the quality of life of the affected individuals. The underlying pathophysiological mechanisms are complex and not yet fully understood, although studies have suggested a multifactorial origin. Proposed factors include viral persistence, immune dysfunction, autoimmunity, endothelial dysfunction, coagulation disturbances, and gut dysbiosis. The identification of these mechanisms could facilitate the development of diagnostic and therapeutic strategies, opening new perspectives for the effective management of persistent Covid. The diagnosis of PC is complex due to the diversity of symptoms and the lack of specific biomarkers. At present, therapeutic approaches focus primarily on symptomatic relief, but further research is required to fully elucidate the mechanisms underlying PC and to develop targeted interventions. This review synthesizes current evidence on the pathophysiological mechanisms of persistent Covid-19, highlighting recent advances and identifying key areas for future research.